Study on Properties of Flame-Retardant Plywood Made with Eucalyptus, Birch and Poplar Wood. Issue 2 (April 2021) - Yin, Chaolu; Zhang, Xiang; Li, Pingli; Fu, Fuxin
Abstract: In this work, the laboratory-made flame-retardant polyvinyl alcohol adhesive was used to prepare flame-retardant plywood made with eucalyptus, birch and poplar respectively, and the effect of tree species on the mechanical properties and flame-retardant properties of flame-retardant plywood was studied. The static bending strength data showed that the tree species had an obvious effect on the mechanical properties of the flame-retardant plywood, the flame-retardant plywood made with eucalyptus had the highest static bending strength, and the sample made with poplar had the lowest static bending strength. The results of the SBI test are consistent with the results of the LOI test, both indicated that the tree species had a significant effect on the flame-retardant properties of the flame-retardant plywood, the flame-retardant plywood made with poplar veneer has the highest LOI value, lowest FIGRA 0.2MJ value and lowest THR 600s value.